Exposure to glyphosate and risk of non-Hodgkin lymphoma and multiple myeloma: an updated meta-analysis - Donato, Francesca (Med Lav, 2020)
OBJECTIVE: We carried out a systematic review and meta-analysis of epidemiologic studies on the association between occupational exposure to glyphosate and risk of non-Hodgkin lymphoma (NHL) and multiple myeloma (MM). METHODS: We conducted a systematic search of the literature, and identified 18 relevant publications, from which we extracted results from seven non-overlapping studies of NHL and three of MM. We performed random-effects meta-analyses for ever-exposure to glyphosate, dose-response, and risk of specific NHL subtypes. RESULTS: The meta-relative risk (RR) of NHL was 1.03 (95% confidence interval [CI] 0.86-1.21), that of MM was 1.04 (95% CI 0.67-1.41). The meta-RR of NHL for highest category of exposure was 1.49 (95% CI 0.37-2.61; 3 studies). The meta-RR for diffuse large B-cell lymphoma (DLBCL) was 1.31 (95% CI 0.93-1.75); that for follicular lymphoma was 0.82 (95% CI 0.93-1.70), and that for chronic lymphocytic leukemia was 0.85 (95% CI 0.20-1.49). There was indication of publication bias for studies on NHL. CONCLUSIONS: Our meta-analysis provided no overall evidence of an increased risk for both NHL and MM in subjects occupationally exposed to glyphosate. In secondary analyses we detected a small increase in risk for the category with highest level of exposure as well as for DLBCL. The evidence of publication bias suggests caution in the interpretation of the results.